Characteristics of pediatric COVID-19 infections and the impact of influenza and COVID-19 vaccinations during the first two years of the pandemic - Ali, Mahmoud; Phillips, Lynette; Kaelber, David C.; Bukulmez, Hulya (Frontiers in Pediatrics, 2023)
The data regarding the SARS-CoV-2 demographics in pediatric population has been published based on several single-center experiences or on metanalyses over short time frames. This article reports data on the demographics of pediatric COVID-19 on a global scale using the TriNetX COVID-19 Research Network. In addition, we address the risk of COVID-19 infection in relation to the body mass index (BMI) and the protective value of Influenza and COVID-19 immunization against COVID-19 infection. The incidence of COVID-19 infection was higher in the younger age group, but there were no gender differences. The incidence of COVID-19 infection was higher among African Americans/Black (28.57%), White race (27.10%), and obese patients across all age groups, in both genders, all races, and ethnicities with overweight/obesity (p < 0.00001). The incidence of MIS-C was also higher in patients with obesity (OR 1.71, CI 1.36,2.14). We found that the patients who were neither vaccinated for COVID-19 nor Influenza within one year before their COVID-19 diagnoses compared to those who received influenza vaccine only had significantly higher odds for hospitalization, development of MIS-C, and more importantly mortality (OR 1.19, CI 1.1-1.28), (OR 1.52, CI 1.32-1.74), (OR 1.15, CI 1.26-1.71) respectively. In addition, those patients who were neither vaccinated for COVID-19 nor Influenza within one year before their COVID-19 diagnoses, compared to those who received at least one dose of COVID-19 vaccine, had significantly higher odds for hospitalization (OR 1.11, CI 1.04-1.19). However, those patients who did not receive the influenza vaccine within one year before their COVID-19 diagnoses nor received the COVID-19 vaccine had much higher odds for hospitalization, MIS-C, and mortality compared to those who received both vaccinations (OR 1.46, CI 1.41-1.51), (OR 3.72, CI 2.11-6.56), (OR 13.55, CI 1.91-9.62) respectively. Using the multiplicative interaction scale, we found a positive interaction between the COVID-19 Vaccine and the Influenza vaccine; they combined have a more significant effect than each separately. Our study is the largest of its kind (to date) examining the global demographic of the pandemic and the first of a kind linking between influenza vaccine and COVID-19-related hospitalization, MIS-C, and mortality in the pediatric population.